Rheological Parameters and Transport Characteristics of Fresh Cement Tailings Backfill Slurry in an Underground Iron Mine - Chi Zhang; Yu-Ye Tan; Kai Zhang; Chun-Yue Zhang; Wei-Dong Song (Advances in Civil Engineering)
Pipeline transportation is the key component of the mine filling system. In this study, fresh cement tailing backfill (CTB) slurry made by unclassified tailings from the Daye iron mine is taken as the research object, and its rheological parameters and transport characteristics are studied via laboratory test and FLUENT software. It was found that the relationship curve of the dynamic yield stress, viscosity, and solid content (SC) of CTB slurry fits the law of the H-B model when SC varies between 60% and 68%. However, the relationship curve gradually changes to fit the Bingham mode when SC reaches up to 70%. Numerical simulation results demonstrate that when the SC of CTB slurry exceeds 65%, the static pressure at the pipeline’s outlet begins to distribute symmetrically. At this point, the slurry flow state is relatively stable, and the pipeline resistance loss is positively correlated with SC and flow rate. When SC exceeds 70%, resistance loss begins to increase significantly. The findings of this study can be used to identify the suitable transportation conditions of CTB slurry and provide the theoretical direction for the pipeline transportation design of filling systems in mines.